The acute effects of heavy back and front squats on speed during forty-meter sprint trials - Yetter, M.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2008)
The purpose of the present study was to investigate the effects of performing heavy back squats (HBS) and heavy front squats (HFS) on the average speed during each 10-m interval of 40-m sprint trials. In a randomized, cross-over design, 10 strength-trained men performed a HBS, HFS, or control treatment before performing three 40-m sprint trials separated by 3 minutes. The HBS and HFS treatments consisted of performing parallel back or front squats with 30%, 50%, and 70% of the subject's 1 repetition maximum after 5 minutes of cycling. The control treatment consisted of cycling for 5 minutes. The sprint trials were performed 4 minutes after completing the HBS, HFS, or control treatments. Significant increases in speed were found during the 10- to 20-m interval for the HBS compared with the control treatment (mean difference, 0.12 m/s; 95% likely range, 0.05-0.18 m/s; P = 0.001). During the 30- to 40-m interval, HBS produced significantly greater speeds compared with the HFS treatment (mean difference, 0.24 m[middle dot]s-1; 95% likely range, 0.02-0.45 m[middle dot]s-1; P = 0.034) and the control treatment (mean difference, 0.18 m[middle dot]s-1; 95% likely range, 0.03-0.32 m/s; P = 0.021). The differing effects of the treatments may reflect different levels of muscular activation or different mechanical aspects of the squat exercises. Similarly, the multidimensional nature of sprint running means that other specific exercises may confer improvements in sprinting performance during other intervals. It is suggested that coaches could incorporate HBS into the warm-up procedure of athletes to improve sprinting performance.